A method for preparing sodium ferrous sulfate positive electrode material and its application in preparing sodium ion battery

By magnetic grinding method, sodium sodium sodium sodium iron is used to solve the problem of lithium ion battery resources and lower capacity of sodium ion battery, and realize the high circulation stability of sodium ion batteries and the improvement of battery capacity.

CN116534901BActive Publication Date: 2025-01-28SHANDONG UNIV OF TECH
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202310049308.4
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2023-02-01
Publication Date
2025-01-28
Estimated Expiration
2043-02-01

AI Technical Summary

Technical Problem

The application of existing lithium-ion batteries in large-scale energy storage technology is restricted by lithium resources, and the specific capacity of sodium-ion batteries is relatively low, so it is necessary to develop a new energy storage battery system with rich resources and cheap prices.

Method used

Use a magnetic grinding method to prepare sodium sulfate sodium iron orthopedic material. By mixing the aqueous sulfate and sodium -free sodium sulfate, it is grinded in the magnetic grinding machine, and then burned in the inert gas atmosphere. Sodium sodium sodium sodium ingot material.

Benefits of technology

Improve the structural stability of sodium sodium sodium sodium iron and ionic engineering, enhance the cycle stability and battery capacity of sodium ion batteries, and significantly improve the efficiency and stability of Kuron.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN116534901B_ABST
    Figure CN116534901B_ABST
Patent Text Reader

Abstract

The invention provides a method for preparing a sodium ferrous sulfate cathode material, and the preparation method is as follows: calcining ferrous sulfate heptahydrate for 5-6 hours under a certain temperature and vacuum conditions to obtain anhydrous ferrous sulfate; uniformly mixing anhydrous ferrous sulfate and anhydrous sodium sulfate with a molar ratio of 1:1 and pouring them into a grinding jar; sealing the grinding jar and putting it into a magnetic grinder for grinding for 2-6 hours; the ground material is heated to 300-400°C at a heating rate of 0.5-5°C / min in an argon atmosphere, and the temperature is kept constant for 10-36 hours to obtain the target material sodium ferrous sulfate. The sodium ion battery ternary cathode material provided by the invention is applied in the preparation of sodium ion batteries, has high capacity, excellent charge and discharge cycle stability and good rate performance, and the synthesis method is low in cost, convenient for industrial control, and has broad market application prospects.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of preparation of positive electrode materials for sodium ion batteries, and in particular to a method for preparing a sodium ferrous sulfate positive electrode material and a sodium ion battery prepared using the prepared material. Background Art

[0002] Coal, oil and natural gas are important natural resources and the main energy sources for our survival. The development and utilization of these traditional fossil energy sources will inevitably bring about environmental pollution and energy crisis problems. Compared with traditional energy sources, new energy sources such as solar energy, wind energy, tidal energy, biomass energy, geothermal energy, etc. have the advantages of less environmental pollution, most of them are renewable, and rich in resources. The development and utilization of these new energy sources is not only an important means to alleviate the problems of environmental pollution and energy depletion in the world today, but also has important strategic significance for solving the war problems caused by energy crises. However, these new renewable energy sources basically have the characteristics of intermittent and randomness. To develop and utilize these new energy sources, it is necessary to develop large-scale energy storage technology.

[0003] The current large-scale energy storage technologies mainly include physical energy storage, electrochemical energy storage, and electromagnetic energy storage (such as superconducting electromagnetic energy storage, etc.) that are being studied and developed. Electrochemical energy storage refers to the energy storage of secondary batteries (rechargeable batteries) that use the reversible principle of electrochemical reactions to achieve the mutual conversion between electrical energy and chemical energy. Electrochemical energy storage has the advantages of low investment, high efficiency, and flexible use, and has become the research focus of scientists. Among them, high-temperature sodium sulfur, all-vanadium liquid flow, and lithium-ion batteries are the most concerned. Although lithium-ion batteries are widely used in computers, communications, electronic equipment, and electric vehicles due to their advantages such as large specific capacity, high voltage, long cycle life, stable discharge performance, low self-discharge rate, wide operating temperature range, safety and pollution-free, and no memory effect, their application in large-scale energy storage technology will eventually be restricted by lithium resources. Therefore, the development of new energy storage battery systems with abundant resources and low prices is the key to the development of today's society and has received widespread attention from scientific researchers. Although the specific capacity of sodium-ion batteries is relatively low compared to other secondary battery alternative systems, such as calcium, magnesium, and aluminum ion battery systems, their abundant resources and similar energy storage principles to lithium-ion batteries make sodium-ion batteries a large-scale energy storage battery technology with great development potential and important research value.

[0004] During the sodium ion insertion and extraction process, the volume change of the material is very small, which makes the sodium ferrous sulfate material have the potential to have a longer cycle life.

[0005] In addition, iron compounds have low toxicity and little environmental pollution. More importantly, my country is the country with the largest iron ore reserves in the world. The rich iron ore resources have become a strong guarantee for my country to develop and utilize iron sulfate positive electrode materials. All of the above advantages indicate that sodium ferrous sulfate is an ideal positive electrode material for sodium ion batteries. Summary of the invention

[0006] The invention provides a method for preparing a sodium ferrous sulfate positive electrode material. The positive electrode material is prepared by a magnetic grinding method. The method is scientific, reasonable, simple and easy to operate, so that the structural stability and ion conductivity are greatly improved. The assembled sodium ion battery has excellent long-cycle stability.

[0007] The technical solution for implementing the present invention is as follows:

[0008] (1) Evenly mix anhydrous ferrous sulfate and anhydrous sodium sulfate in a molar ratio of 1:1 and pour into a grinding tank;

[0009] (2) Seal the grinding jar and place it in a magnetic grinder for 2-6 hours;

[0010] (3) The weighed and ground material is calcined in an inert gas atmosphere at a calcination temperature of 200-400° C. to obtain the target material, sodium ferrous sulfate.

[0011] Furthermore, the preparation method of anhydrous ferrous sulfate is to calcine ferrous sulfate heptahydrate at 150-220° C. under vacuum conditions for 5-6 hours to obtain anhydrous ferrous sulfate.

[0012] Furthermore, in step (3), the inert gas is argon.

[0013] Furthermore, in step (3), a crucible or a porcelain boat may be used for calcination.

[0014] Furthermore, in step (3), the calcination is carried out by heating the temperature to 200-400°C at a heating rate of 0.5-5°C / min and maintaining the temperature for 6-36 hours.

[0015] Application of sodium ferrous sulfate positive electrode material prepared by the above method in the preparation of sodium ion batteries.

[0016] Beneficial effects of the present invention:

[0017] 1. The present invention first performs a water removal treatment on ferrous sulfate heptahydrate to ensure that the material does not contain water and does not come into contact with water during the entire process, so that the material is always in a dry environment, thereby avoiding the loss of sulfate during calcination;

[0018] 2. The present invention performs magnetic grinding on the materials, and the materials can be fully and evenly mixed under the action of the magnetic field; the obtained positive electrode material has a regular microscopic morphology and a smaller particle size, and its three-dimensional sodium ion transmission channel is more conducive to the diffusion of sodium ions. The sodium ion battery assembled with the positive electrode material prepared by the magnetic grinding method is subjected to charge and discharge and rate performance tests. The results show that the magnetic grinding technology can effectively improve the cycle stability of the sodium ion battery. BRIEF DESCRIPTION OF THE DRAWINGS

[0019] Figure 1 This is the X-ray diffraction pattern of the sodium ferrous sulfate positive electrode material prepared in Example 2.

[0020] Figure 2 This is a scanning electron microscope (SEM) image of the sodium ferrous sulfate positive electrode material prepared in Example 2.

[0021] Figure 3 It is a rate performance diagram of a sodium ion battery prepared using the sodium ferrous sulfate positive electrode material prepared in Example 2 and Comparative Example 2.

[0022] Figure 4 It is a charge and discharge cycle performance diagram of a sodium ion battery prepared using the sodium ferrous sulfate positive electrode material prepared in Example 2 and Comparative Example 2. DETAILED DESCRIPTION

[0023] The following is a further detailed description of the present invention in combination with specific implementation methods, and it cannot be determined that the specific implementation of the present invention is limited to these descriptions. For ordinary technicians in the technical field to which the present invention belongs, several simple changes or substitutions can be made without departing from the concept of the present invention, which should be regarded as falling within the scope of protection of the present invention.

[0024] Example 1

[0025] This embodiment includes the following steps:

[0026] Preparation of sodium ferrous sulfate positive electrode material:

[0027] (1) Put 2.4 g of sodium sulfate and 2.6 g of ferrous sulfate into the same mortar and grind them evenly to obtain a mixture of the two materials;

[0028] (2) Pour 100 g of steel needles into a magnetic grinding jar first, and then pour in the above mixture;

[0029] (3) sealing the magnetic grinding jar and setting the magnetic grinding for 4 hours to obtain the precursor material after the grinding;

[0030] (4) After the precursor material is cooled, it is ground for 5 minutes, and an appropriate amount of the precursor material is placed in a porcelain boat, which is then transferred to an argon atmosphere tubular furnace, heated to 300°C at a heating rate of 1°C / min, and calcined for 12 hours to obtain a sodium ferrous sulfate positive electrode material.

[0031] Preparation of sodium ion battery: Sodium ferrous sulfate positive electrode material, Ketjen black, and PVDF were dispersed and stirred at a mass ratio of 8:1:1 for 1 h to prepare a conductive slurry.

[0032] Example 2

[0033] This embodiment includes the following steps:

[0034] Preparation of sodium ferrous sulfate positive electrode material:

[0035] (1) Put 2.4 g of sodium sulfate and 2.6 g of ferrous sulfate into the same mortar and grind them evenly to obtain a mixture of the two materials;

[0036] (2) Pour 100 g of steel needles into a magnetic grinding jar first, and then pour in the above mixture;

[0037] (3) sealing the magnetic grinding jar and setting the magnetic grinding for 4 hours to obtain the precursor material after the grinding;

[0038] (4) After the precursor material is cooled, it is ground for 5 minutes, and an appropriate amount of the precursor material is placed in a porcelain boat, transferred to an argon atmosphere tubular furnace, heated to 350°C at a heating rate of 1°C / min, and calcined for 12 hours to obtain a sodium ferrous sulfate positive electrode material.

[0039] Preparation of sodium ion battery: Sodium ferrous sulfate positive electrode material, Ketjen black, and PVDF were dispersed and stirred at a mass ratio of 8:1:1 for 1 h to prepare a conductive slurry.

[0040] Figure 1 The standard card PDF#21-1360 and XRD diagram of Na2Fe(SO4)2 of the target product obtained in Example 2 show that the main component of the target product is Na2Fe(SO4)2 and has good crystallinity.

[0041] Figure 2 This is the SEM image of the target product obtained in Example 2, from which it can be seen that the particles are evenly distributed.

[0042] Example 3

[0043] This embodiment includes the following steps:

[0044] Preparation of sodium ferrous sulfate positive electrode material:

[0045] (1) Put 2.4 g of sodium sulfate and 2.6 g of ferrous sulfate into the same mortar and grind them evenly to obtain a mixture of the two materials;

[0046] (2) Pour 100 g of steel needles into a magnetic grinding jar first, and then pour in the above mixture;

[0047] (3) sealing the magnetic grinding jar and setting the magnetic grinding for 4 hours to obtain the precursor material after the grinding;

[0048] (4) After the precursor material is cooled, it is ground for 5 minutes, and an appropriate amount of the precursor material is placed in a porcelain boat, transferred to an argon atmosphere tubular furnace, heated to 400°C at a heating rate of 1°C / min, and calcined for 12 hours to obtain a sodium ferrous sulfate positive electrode material.

[0049] Preparation of sodium ion battery: Sodium ferrous sulfate positive electrode material, Ketjen black, and PVDF were dispersed and stirred at a mass ratio of 8:1:1 for 1 h to prepare a conductive slurry.

[0050] Comparative Example 1

[0051] This embodiment includes the following steps:

[0052] Preparation of sodium ferrous sulfate positive electrode material:

[0053] (1) Put 2.4 g of sodium sulfate and 2.6 g of ferrous sulfate into the same mortar in batches and grind them evenly to obtain a mixture of the two materials;

[0054] (2) placing the mixture into a ball mill, sealing the ball mill, starting the grinder, and grinding for 4 hours to obtain a precursor material;

[0055] (3) After the precursor material is cooled, it is ground for 5 minutes, and an appropriate amount of the precursor material is placed in a porcelain boat, which is then transferred to an argon atmosphere tubular furnace, heated to 300°C at a heating rate of 1°C / min, and calcined for 12 hours to obtain a sodium ferrous sulfate positive electrode material.

[0056] Preparation of sodium ion battery: Sodium ferrous sulfate positive electrode material, Ketjen black, and PVDF were dispersed and stirred at a mass ratio of 8:1:1 for 1 h to prepare a conductive slurry.

[0057] Comparative Example 2

[0058] This embodiment includes the following steps:

[0059] Preparation of sodium ferrous sulfate positive electrode material:

[0060] (1) Put 2.4 g of sodium sulfate and 2.6 g of ferrous sulfate into the same mortar in batches and grind them evenly to obtain a mixture of the two materials;

[0061] (2) placing the mixture into a ball mill, sealing the ball mill, starting the grinder, and grinding for 4 hours to obtain a precursor material;

[0062] (3) After the precursor material is cooled, it is ground for 5 minutes, and an appropriate amount of the precursor material is placed in a porcelain boat, transferred to an argon atmosphere tubular furnace, heated to 350°C at a heating rate of 1°C / min, and calcined for 12 hours to obtain a sodium ferrous sulfate positive electrode material.

[0063] Preparation of sodium ion battery: Sodium ferrous sulfate positive electrode material, Ketjen black, and PVDF were dispersed and stirred at a mass ratio of 8:1:1 for 1 h to prepare a conductive slurry.

[0064] Comparative Example 3

[0065] This embodiment includes the following steps:

[0066] Preparation of sodium ferrous sulfate positive electrode material:

[0067] (1) Put 2.4 g of sodium sulfate and 2.6 g of ferrous sulfate into the same mortar in batches and grind them evenly to obtain a mixture of the two materials;

[0068] (2) placing the mixture into a ball mill, sealing the ball mill, starting the grinder, and grinding for 4 hours to obtain a precursor material;

[0069] (3) After the precursor material is cooled, it is ground for 5 minutes, and an appropriate amount of the precursor material is placed in a porcelain boat, transferred to an argon atmosphere tubular furnace, heated to 400°C at a heating rate of 1°C / min, and calcined for 12 hours to obtain a sodium ferrous sulfate positive electrode material.

[0070] Preparation of sodium ion battery: Sodium ferrous sulfate positive electrode material, Ketjen black, and PVDF were dispersed and stirred at a mass ratio of 8:1:1 for 1 h to prepare a conductive slurry.

[0071] contrast Figure 3 and Figure 4 When the rate is gradually increased, the capacity of the battery prepared by magnetic grinding technology decays slowly and the capacity retention rate is high, while the battery capacity of the battery prepared by ball milling technology is low, the capacity retention rate is low and the decay is fast. At the same rate of 0.5C, the battery prepared by ball milling technology has low capacity, instability and poor performance, while the magnetic grinding technology greatly improves the battery capacity, the coulomb efficiency is high and stable, and the effect is unexpectedly good. It is speculated that the reason may be that magnetic grinding can strengthen the interaction between several raw materials.

[0072] By comparing the two sets of pictures, without adding other materials, for the same batch of materials, the battery prepared by magnetic grinding technology has larger capacity, higher efficiency and more stable overall performance than the battery prepared by ball milling technology. In terms of the choice of preparation process, magnetic grinding technology has more potential.

Claims

1. A method for preparing a sodium ferrous sulfate positive electrode material, comprising the following steps: (1) Evenly mix anhydrous ferrous sulfate and anhydrous sodium sulfate in a molar ratio of 1:1 and pour into a grinding tank; (2) After sealing the grinding jar, place it in a magnetic grinder and grind for 2-6 hours; (3) The weighed and ground material is calcined in an inert gas atmosphere at a calcination temperature of 200-400° C. to obtain the target material, sodium ferrous sulfate.

2. The preparation method according to claim 1, characterized in that: In step (3), the inert gas is argon.

3. The preparation method according to claim 1, characterized in that In step (3), a crucible or a porcelain boat is used for calcination.

4. The preparation method according to claim 1, characterized in that In step (3), the calcination is carried out by heating the temperature to 300-400° C. at a heating rate of 0.5-5° C. / min and maintaining the temperature for 10-36 hours.

5. The preparation method as described in claim 1, characterized in that The preparation method of the anhydrous ferrous sulfate used is: calcining ferrous sulfate heptahydrate at 150-220° C. under vacuum conditions for 5-6 hours to obtain anhydrous ferrous sulfate.

6. Use of the sodium ferrous sulfate positive electrode material prepared by the preparation method according to any one of claims 1 to 5 in the preparation of sodium ion batteries.

Citation Information

Patent Citations

  • Positive electrode material for sodium ion battery and preparation method of positive electrode material

    CN114597365A